Pre-treatment microbial Prevotella-to-Bacteroides ratio, determines body fat loss success during a 6-month randomized controlled diet intervention - Hjorth, M F; Roager, H M; Larsen, T M; Poulsen, S K; Licht, T R; Bahl, M I; Zohar, Y; Astrup, A (International Journal of Obesity, 2018)
On the basis of the abundance of specific bacterial genera, the human gut microbiota can be divided into two relatively stable groups that might have a role in personalized nutrition. We studied these simplified enterotypes as prognostic markers for successful body fat loss on two different diets. A total of 62 participants with increased waist circumference were randomly assigned to receive an ad libitum New Nordic Diet (NND) high in fiber/whole grain or an Average Danish Diet for 26 weeks. Participants were grouped into two discrete enterotypes by their relative abundance of Prevotella spp. divided by Bacteroides spp. ( P/B ratio) obtained by quantitative PCR analysis. Modifications of dietary effects of pre-treatment P/B group were examined by linear mixed models. Among individuals with high P/B the NND resulted in a 3.15 kg (95% confidence interval (CI): 1.55; 4.76, P <0.001) larger body fat loss compared with ADD, whereas no differences was observed among individuals with low P/B (0.88 kg (95% CI: −0.61; 2.37, P =0.25)). Consequently, a 2.27 kg (95% CI: 0.09; 4.45, P =0.041) difference in responsiveness to the diets were found between the two groups. In summary, subjects with high P/B ratio appeared more susceptible to lose body fat on diets high in fiber and whole grain than subjects with a low P/B ratio.